Study of the churches of the city of Ibarra, Imbabura-Ecuador - Coronado Martín, Jesús Ángel; Cala Aiello, Olga (Estoa. Journal of the Faculty of Architecture and Urbanism, 2017)
An analysis of the current state of the churches in Ibarra, rebuilt from the year 1868 after the earthquake and the ones build after takes place, is conducted in order to determine the evolution in terms of parameters such as the spatial configuration and use of building materials, both inside space and facade. Records of every church, including floor plans, photographs of the current state and description of the architectural configuration, structural materials, main facade, interior finishes and cover are made. Data collection are done through a bibliographical analysis and field research corroborated the data obtained in the revised documentation. Exists a chronological evolution in the typology of churches: basilica, vaulted room with a flat roof and unique space, as happens on the facades, giving those different treatments, depending on the time when they were built. Keywords: architectural configuration, carved stone, construction, facade, interior space vault.